ANALISIS KELAYAKAN ISI BUKU TEKS “MARDIKA BASA LAN SASTRA JAWA” KELAS VII - Nissa Kusuma Wardani; Kenfitria Diah Wijayanti; Budi Waluyo (Universitas Sebelas Maret, 2025)
Textbooks are books that serve as guidelines for the teaching and learning process, one of which is the Class VII Javanese language textbook with the title